Consumer Behaviour Towards Branded Sunglasses Amongst The Students Of Kottayam City (Journal of Informatics Education and Research, 2025)
Recent studies show that marketers are increasingly emphasizing branding, believing that a well-established brand can more effectively influence consumer decisions. Branding does not operate in isolation—integrated marketing communication plays a key role in shaping consumer preferences. This study investigates consumer behavior towards branded sunglasses, focusing on student preferences in Kottayam city. Primary data was collected from 130 student respondents using a structured questionnaire. Secondary data was sourced from journals, e-newspapers, and websites to support and interpret the findings. The research aims to understand customer perception and brand consciousness in choosing sunglasses, and to identify factors influencing buying decisions. Hypothesis testing was conducted to examine the impact of demographic factors on brand selection. Results indicate that quality and social image significantly affect brand choice, while price has minimal influence. The findings offer valuable insights for marketers and future research in consumer behavior.